(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: Review some social characteristics of patients who have undergone an induced abortion at 17 to 22 weeks of pregnancy with Misoprostol-only at the Hanoi Obstetrics and Gynecology Hospital. Materials and method: A cross-sectional study was conducted on 154 pregnant with gestational age from 17 to 22 weeks whose pregnancies terminated with Misoprostole-only at Hanoi Obstetrics and Gynecology Hospital from January to December 2022. Results: The average age of the pregnancies in the study was 27.9 ± 7.0 years, with the youngest being 14 years old and the oldest being 50 years old. The majority of the pregnancies had a high level of education, accounting for 63%, and 30.5% were civil servants, with 66.9% being married. Induced abortion using Misoprostol-only was largely administered to nulliparous or primiparous women (64.9%), who had not undergone an abortion or had only one previous abortion (90.3%). In our study, the primary reason for induced abortion was fetal abnormalities (48.1%) with an average gestational age of 19.5 ± 1.6 weeks, which was quite similar to the average gestational age of the group undergoing abortion for other reasons (19.6 ± 1.6 weeks). Conclusion: The majority of the pregnancies in our study were in the adult age group (19-35), accounting for 74.7%, were married (66.9%), and had a high level of education (63%). Induced abortion using Misoprostol-only was commonly prescribed for primiparous women or those with one child (64.9%), who had undergone abortion less than once before (90.3%). The primary reason for induced abortion at 17-22 weeks of gestation was primarily due to fetal abnormalities (48.1%), with no significant difference in gestational age compared to the group with other reasons.